Hubungan Dukungan Sosial Keluarga dengan Gejala Post Traumatik Stress Disorder (Habibah) Cronic pada Korban Bencana Banjir di Desa Parerejo - Sari, Hanna Vina; Agustriyani, Feri; Ardinata, Ardinata; Wijayanto, Wisnu Probo; Mukhlis, Hamid (Penerbit Goodwood, 2023)
Purpose: This study investigates the correlation between family social support and chronic Post-Traumatic Stress Disorder (PTSD) symptoms among flood victims in Parerejo Village. Pre-survey data showed varied PTSD symptom levels, with most respondents experiencing moderate to severe trauma. Research methodology: The research design employed in this study was a correlation analysis using a cross-sectional method. The sample size for this study was 72 flood victims from Parerejo Village, RT. 11 (Neighborhood Association number: 11). The bivariate analysis in this study utilized Spearman’s rho test. Results: The research design employed in this study was a correlation analysis using a cross-sectional method. The sample size for this study comprised 72 flood victims from Parerejo Village, RT. 11 (Neighborhood Association number 11). The bivariate analysis in this study utilized the Spearman Rho test. Conclusions: Family social support plays a critical role in alleviating chronic PTSD symptoms among disaster victims. Strengthening familial ties and promoting emotional support in the household may be an effective strategy for post-disaster mental health recovery. Limitations: This study is limited by its cross-sectional design, which restricts causal inference. The use of a localized sample from a single neighborhood also limits the generalizability of the findings to broader populations. Contribution: This research contributes to the field of disaster psychology by providing empirical evidence on the protective influence of family-based social support in mitigating long-term PTSD symptoms. The findings can inform mental health interventions and disaster recovery programs, emphasizing the need to involve families in psychosocial rehabilitation efforts.